THE ROLE OF ECLAC –FAO IN RESPONDING TO THE POST-PANDEMIC ERA THROUGH THE TRANSFORMATION OF FOOD AND AGRICULTURE IN LATIN AMERICA AND THE CARIBBEAN REGION 2020-2022 - Adim Seto Ali Masquri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
This paper seeks to determine the role of the Economic Commission for Latin America and the caribbean (ECLAC) and the Food and Agriculture Organization (FAO) in responding to the post-pandemic era through the transformation of food and agriculture in LAC Region. The COVID-19 pandemic, which began in early 2020, has shaken global stability related to food and agriculture issues, especially in LAC region. The agricultural sector is an important sector in LAC region that acts as the basis for food production and ecosystems in the region. Regional and international organizations such as the Economic Commission for Latin America and the Caribbean (ECLAC) and the Food and Agriculture Organization (FAO) have attempted to recovering the agricultural and food sectors from the impacts of the COVID pandemic. The method used is qualitative, with data sources from books, journals, and other official media. These findings illustrate the role of the ECLAC and FAO organizations in transforming agriculture and food in LAC region after the COVID pandemic. Novelty – The post COVID-19 agriculture and food transformation strategy implemented by ECLAC and FAO in LAC region has become an important factor for the region. This can provide input for the governments of countries in LAC region in taking appropriate policies for countries in the region. Keywords: Post Covid-19; Food and Agriculture; Latin America and the Caribbean